2022
DOI: 10.1111/jam.15434
|View full text |Cite
|
Sign up to set email alerts
|

Expression of thurincin H, ChiA74 and Cry proteins at the sporulation phase in Bacillus thuringiensis HD1

Abstract: Aims:The objective of this study was to produce thurincin H, ChiA74 and Cry proteins together using Bacillus thuringiensis subsp. kurstaki HD1 as a heterologous host. Methods and Results: pSTAB-ThurH and pSTAB-ChiA74 constructs were designed to produce thurincin H and chitinase, respectively, at the sporulation phase.They were transformed into Bt HD1 generating the recombinant strains HD1/ pSTAB-ThurH and HD1/pSTAB-ThurH/pSTAB-ChiA74. Antimicrobial and chitinolytic activity tests were performed with recombinan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 30 publications
(48 reference statements)
0
3
0
Order By: Relevance
“…Figures were plotted using GraphPad Prism 6 (GraphPad Software, CA, USA). Dose-mortality data were analyzed using the probit method according to Finney (Finney 1971). The slope and intercept of the dose-response curve were estimated using SPSS v22.0, and the LC 20 (Lethal Concentration for 20%), LC 50 (Lethal Concentration for 50%) values of the different insecticides for each pest were evaluated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Figures were plotted using GraphPad Prism 6 (GraphPad Software, CA, USA). Dose-mortality data were analyzed using the probit method according to Finney (Finney 1971). The slope and intercept of the dose-response curve were estimated using SPSS v22.0, and the LC 20 (Lethal Concentration for 20%), LC 50 (Lethal Concentration for 50%) values of the different insecticides for each pest were evaluated.…”
Section: Discussionmentioning
confidence: 99%
“…Most of the isolated strains showed catalase amylohydrolysis and indole properties (Table 2), which are consistent with the physiological and biochemical characteristics of Bt subsp. kurstaki strain HD-1 (Ref) (Porcar et al 2000, Porcar et al 2003, Ardahan Eski et al 2018, Gaona Mendoza et al 2021, Park et al 2022). In the present study, 11 general primers previously used for cry gene identification in lepidopteran pests were used.…”
Section: Discussionmentioning
confidence: 99%
“…Bacteria produce bacteriocins at the ribosomal level, and it has been reported that more than 99% of these microorganisms are able to synthesize these AMPs (Riley & Wertz, 2002). Bacteriocins have been used as food preservatives, in health to treat bacterial infections, as spermicidal agents, anticancer agents, for skin and oral care, in nutrition as modulators of the gastrointestinal microbiota, and in agriculture as biocontrol agents and plant growth promoters (Cesa‐Luna et al, 2021; Gaona‐Mendoza et al, 2021; Negash & Tsehai, 2020). Bacteriocins produced by lactic acid bacteria (LAB), primarily those used as probiotic, have been studied extensively (Alvarez‐Sieiro et al, 2016).…”
Section: Introductionmentioning
confidence: 99%